A geografia escolar: referencial para interpretação do vivido? - Viviane Cristina de Paula (2017)
The objective of this work was to obtain indicatives about the teaching practices of the Geography teacher that permeate the experiences lived in the students' daily life, in the treatment of social and environmental issues. The interest for this research was based on the professional experience of this researcher in a Conservation Unit (UC) - Biribiri State Park (PEBI), located in the town of Diamantina, in which she had the function of developing Environmental Education activities in the schools located around this Conservation Unit. However, during her experience, the researcher realized that the teacher of Geography, as a rule, when approaching the content of the discipline, presented some distance in dealing with the local scale in the approach of the geographic concepts, which were most often on the global scale. Taking into account that the approaches of Geography education in schools, based on the academic debates and educational policies developed over the last two decades, have affirmed the necessary adherence to pedagogical practices that allow students to interpret the spatiality of the most diverse phenomena. Moreover, for this, it is considered necessary that the Geography teacher has a teaching practice that goes beyond the transmissive pedagogical model, to that of mediator and generator of reflections that benefit the students in the apprehension of questions concerning their context of life. It was fundamental to investigate how Geography teachers appropriate (or not) the scalar reference of the place in their educational actions. With the support of these ideas, it was searched, through the continuous dialogue with the specialized literature, the development of the direct observation of the pedagogical practice and the execution of an interview. In this interview, there was inference of data referring to the discourse of the teacher, who was the subject of the research, with the purpose of emerging if the processes interactions in the classroom enabled to bring the contents and theories of Geography closer to the daily life of the students. In addition, the documentary research (textbook and teaching plan) allowed identifying if her teaching methodologies established relations with the lived / local context of the students. The data revealed that, although the teacher, subject of the research, used references of the lived, for many times the speeches and methods used in class did not deal with social and environmental issues comprehensively. In addition, the processes and concepts moved in the direction of restricting themselves in punctual and fragmented activities, disconnected from reality, restricting possibilities of interactions and relationships between the content and the living space by students.